'Going agile': Exploring the use of project management tools in fostering psychological safety in group work within management discipline courses. Issue 3 (November 2021) - Marder, Ben; Ferguson, Pauline; Marchant, Caroline; Brennan, Mary; Hedler, Caroline; Rossi, Marco; Black, Shona; Doig, Rona
Abstract: While psychological safety is widely acknowledged to be a crucial factor in determining how well teams function, little attention has been paid to this phenomenon in management education and HE more broadly. This highlights an important gap, given the 'thorny' nature, and pervasive use, of group work. We contribute the first examination of an HE intervention to increase psychological safety. Specifically, through a two-phase mixed methods approach (pre/post surveys and focus groups, student diaries), we examine the implementation of Agile project management principles in both an undergraduate and postgraduate digital marketing course (total n = 131). The findings illustrate that the intervention increased psychological safety along with team-performance, group learning, interpersonal communication and creativity, whilst also reducing the free-rider problem. The study provides three contributions. First, we extend knowledge of psychological safety by showing it can be fostered through interventions providing two core antecedents (supporting facilitation and a cohesive framework). Second, we build knowledge of psychological safety in education by evidencing a greater breadth of positive outcomes, which until now has been mostly limited to knowledge development. Third, we expand understanding of implementing group work interventions in management, providing five important considerations for educational practitioners. Highlights: Agile working is common in industry teams but is not adopted by HE student teams. Using the SCRUM methodology increases psychological safety in student teams. Increased psychological safety, increases team performance, learning and creativity. Increased psychological safety reduces the free-riding problem. Directions for initiating Agile working in student teams is provided.